EDUGAMES PEMBELAJARAN MATEMATIKA BERBASIS ANDROID UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK - helsa, yullys; Maryam Rohimah, Siti; Pramudiani, Puri (SIGMA DIDAKTIKA: Jurnal Pendidikan Matematika, 2021)
This study aims to develop learning media in the form of android-based learning edugames that can encourage the improvement of students' critical thinking skills. The development of this learning media is carried out for fourth grade elementary school students on fraction material using Unity3d and Photoshop applications. The media development process includes four stages, namely the stage of problem analysis, determining requirements, designing and developing the product, and evaluating the product. After being developed, the learning media was then validated and tested to investigate the validity and practicality of the developed product. The validation results show that the media gets a score of 61 in the high category. The results of the practicality test from the teacher and student aspects respectively obtained a percentage of 79.17% (practical) and 90.7% (very practical). This shows that the android-based learning media developed is feasible and practical to use. Thus, this android-based learning media can be an alternative learning media that can be utilized by teachers at the elementary school level which encourages the improvement of students' critical thinking skills.